The Internet of Battle Things (IoBT) – Perception and Adoption of Special Operation Agents : Case Study of Counter Terrorist Operations Center - Noonlaong, Jirawat; Pisarn, Chutima (SAU JOURNAL OF SCIENCE & TECHNOLOGY, 2025)
The objectives of this study were to 1) Examine the factors influencing the perception of Internet of Battle Things (IoBT) technology among special operation agents of the Counter Terrorist Operations Center (CTOC). 2) Examine the factors influencing the adoption of IoBT technology among special operation agents of the CTOC. This research employed both quantitative and qualitative methods. For the quantitative part, a questionnaire was used to collect data from all 104 special operation agents of CTOC. For the qualitative part, in-depth interviews were conducted with 5 commanders. The data were analyzed using descriptive statistics, including percentage, arithmetic mean, and standard deviation. Hypothesis testing was conducted through mean comparison using the Independent Samples T-Test and One-Way Analysis of Variance (ANOVA). The findings revealed that personal factors had no statistically significant effect on either the perception or adoption of IoBT technology among special operation agents at the 0.05 significance level. Furthermore, the commanders proposed guidelines for the development of personnel in the area of information technology, as well as recommendations for the safe and effective use of IoBT technology. These insights can serve as valuable input for the future development of personnel, equipment, and organizational capabilities.